Better worm control for goats and sheep in the Philippines - Gray, G.D.; Ancheta, P.A.; Arguzon, J.A.; Barcelo, P.M.; Casis, C.; Cerbito, W.A.; Dobson, R.J.; Dumilon, R.; Cruz, E.M.; Knox, M.R.; LeJambre, L.F.; Mateo, K.S.; et al. (Asian-Australasian Association of Animal Production Societies, 2000)
Presents the objective of the programme, viz., to implement currently available options for nematode control including rotational grazing systems and identification of effective dewormers. Preliminary results on these are presented here. Research on the identification of resistants genotypes is in progress.